Calibration of remote nanothermometers using nanoparticles of NaYF 4 : Er 3+ , Yb 3+ , Nd 3+ - Vásquez Mazzotti D. (2018)
This work has been financed by the FONDECYT-CONCYTEC (agreements No. 167 and No.168) and developed in the Photonics Laboratory of the Faculty of Sciences of the Universidad Nacional de Ingenier´ıa